THE JAVANESE SPECIES OF TETRAPLOA - Rifai, Mien A.; Zainuddin, Hardaniah; Cholil, Abdul (Research Center for Biology, 1988)
Two species of the hyphomycete genus Tetraploa are reported from Java, namely the widespread Tetraploa aristata and the newly described Tetraploa javanica. Illustrated descriptions are presented for both species.